Detailed structure of the venous drainage of the brain: relevance to accidental and non-accidental traumatic head injuries - Nakagawa, Seneka (2014)
This project aimed to prove the existence of fine subdural veins hypothesised to be the source of intracranial bleeding seen in cases of accidental and non-accidental traumatic head injuries, and consequently illustrate their anatomical structure. This was important in contributing towards establishing the causal mechanism for traumatic intracranial bleeding, and was particularly applicable in unexplained traumatic head injuries in cases of possible child abuse. These issues are on-going, worldwide concerns that have been of public as well as scientific concern for many years.